2019
DOI: 10.3892/ijo.2019.4924
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance‑related sunitinib sequestration in autophagolysosomes of endothelial cells

Abstract: Our previous study demonstrated that the tyrosine kinase receptor inhibitor sunitinib induces acquired drug resistance in endothelial cells. The present study explored the role of lysosomal sequestration of sunitinib in the acquisition of drug resistance in human microcapillary endothelial HMEC-1 cells. Resistance was induced by escalating concentrations of sunitinib and a shift in IC50 from 12.8 to >20 µM was detected. The results of time-lapse fluorescence microscopy illustrated an instantaneous emergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Lysosomal sequestration is a reversible resistance mechanism. A study conducted in sunitinib resistant RCC cells revealed that lysosomal function was suppressed when sunitinib was withdrawn from the cell cultures and drug sensitivity was retrieved [ 150 ]. Furthermore, alkalinizing lysosomes with an H+-ATPase inhibitor like bafilomycin has been also studied for reversing sunitinib resistance since pH gradient plays a key role in its sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal sequestration is a reversible resistance mechanism. A study conducted in sunitinib resistant RCC cells revealed that lysosomal function was suppressed when sunitinib was withdrawn from the cell cultures and drug sensitivity was retrieved [ 150 ]. Furthermore, alkalinizing lysosomes with an H+-ATPase inhibitor like bafilomycin has been also studied for reversing sunitinib resistance since pH gradient plays a key role in its sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lysosomal sequestration is a reversible process [169,170]. Studies on sunitinib-resistant RCC tumour cell lines have shown that sensitivity to the drug was regained and the lysosome capacity reversed after the cells were cultured without sunitinib [171].…”
Section: Lysosomal Sequestration Of Drugsmentioning
confidence: 99%
“…Some mechanisms of tumor resistance to drugs are mediated by lysosome; as is the case with the lysosomal sequestration of multiple weak-base hydrophobic drugs, including tyrosine kinase inhibitors (e.g., sunitinib) ( Gotink et al., 2011 ). Such organelle-mediated drug sequestration keeps these drugs away from their intracellular sites, hence resulting in tumor resistance ( Wu et al., 2020 ). The approved drug pantoprazole used for the management of gastroesophageal reflux disease significantly increases the sensitivity of tumor xenografts to paclitaxel by inhibiting autophagy ( Tan et al., 2017 ).…”
Section: Modulation Of Autophagy As Cancer Therapymentioning
confidence: 99%